The Element shlm in Hebrew Personal Names in the Land of Israel during the Iron Age ii Period - Golub, Mitka R. (Vetus Testamentum, 2015)
In this study, I investigated all personal names with the element שלם in the Land of Israel during the Iron Age ii period. I collected the names from archaeological and biblical sources, analyzed and compared their distribution according to geography, chronology, and political affiliation. The results show that while שלם is a popular element in Judah from the eighth to the early sixth centuries, it is absent from Israel. The element שלם in unvocalized names from archaeological sources is interpreted mostly as ‘replacement, substitute’ (for the deceased child). However, the popularity of the element שלם solely in Judah may indicate that שלם was used more often than we assume as a divine name referring to YHWH, as do all other Judean popular names. In addition, the comparison between the names from archaeological and biblical sources may be interpreted to indicate that the Bible reflects Judean and not Israelite onomastic traditions.